IncobotulinumtoxinA for Aesthetic Indications: A Systematic Review of Prospective Comparative Trials. Issue 7 (July 2017) - Prager, Welf; Nogueira Teixeira, Diana; Leventhal, Phillip S.
Abstract : BACKGROUND: IncobotulinumtoxinA is a botulinum toxin type A (BoNTA) indicated for temporary improvement in the appearance of upper facial lines with well-established efficacy and safety profiles. Whether incobotulinumtoxinA and other BoNTAs are equipotent is subject of debate. OBJECTIVE: To compare the efficacy of incobotulinumtoxinA and other BoNTAs for aesthetic applications. MATERIALS AND METHODS: PubMed and Embase were systematically searched for prospective clinical trials comparing incobotulinumtoxinA with onabotulinumtoxinA, abobotulinumtoxinA, or placebo for aesthetic applications. RESULTS: Fifteen articles met the selection criteria. Two studies found that incobotulinumtoxinA was noninferior or equivalent to onabotulinumtoxinA for the treatment of glabellar frown lines (GFLs). Eight studies found no difference in efficacy between incobotulinumtoxinA and other BoNTAs. One study suggested differences in response rates at certain time points between incobotulinumtoxinA and onabotulinumtoxinA for GFLs, and one suggested differences for dynamic horizontal forehead lines but not for GFLs or lateral periorbital lines, but both had study design issues limiting the ability to draw conclusions. Finally, 3 placebo-controlled studies demonstrated the efficacy of incobotulinumtoxinA for treating GFLs and upper facial lines. CONCLUSION: The weight of the evidence from comparative clinical trials indicates that incobotulinumtoxinA, onabotulinumtoxinA, and abobotulinumtoxinA have similar efficacy for aesthetic applications. Abstract : Supplemental Digital Content is Available in the Text.